2014
DOI: 10.1519/jsc.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Technical-Tactical Analysis of Youth Olympic Taekwondo Combat

Abstract: The purpose of this study was to define the technical and tactical profiles of official youth taekwondo competitions played under the most recent rules of the International Taekwondo Federation. Tactical actions (i.e., attack, defense, and block), technical executions (from 1- to 4-point scores), kicking legs (i.e., front/rear and right/left), and overall technical effectiveness were investigated in relation to match outcome of semifinal and final competitions (n = 50) of youth (aged 13-14 years) black belt at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 14 publications
5
33
0
13
Order By: Relevance
“…A Tabela 2 mostra estudos com protocolos sofisticados que identificaram e caracterizam ações de combate complexos de serem desenvolvidos e replicados, pois dependem da precisão no relato dos critérios da observação técnico-tática Casolino, et al, 2012;Kazemi, et al, 2013). Merecem destaques quatro artigos selecionados com direcionamento específico para análise de time-motion ou/e técnica e tática em revistas internacionais com fator de impacto maior que 1.0 (Tornello, et al, 2013;Bridge, et al, 2011;Santos, et al, 2011;Tornello, et al, 2014). Essas investigações conduziram estudos com validade externa elevada e apresentaram maiores evidências de validade interna quanto aos procedimentos avaliados na escala de PEDro.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A Tabela 2 mostra estudos com protocolos sofisticados que identificaram e caracterizam ações de combate complexos de serem desenvolvidos e replicados, pois dependem da precisão no relato dos critérios da observação técnico-tática Casolino, et al, 2012;Kazemi, et al, 2013). Merecem destaques quatro artigos selecionados com direcionamento específico para análise de time-motion ou/e técnica e tática em revistas internacionais com fator de impacto maior que 1.0 (Tornello, et al, 2013;Bridge, et al, 2011;Santos, et al, 2011;Tornello, et al, 2014). Essas investigações conduziram estudos com validade externa elevada e apresentaram maiores evidências de validade interna quanto aos procedimentos avaliados na escala de PEDro.…”
Section: Resultsunclassified
“…Entre 2000 e 2004, os atletas de ambos os sexos pontuaram mais utilizando técnicas de ataque de chute (Kazemi, et al, 2006(Kazemi, et al, , 2009, assim como observado com atletas juvenis (Casolino, et al, 2012). Porém, em 2008, os atletas pontuaram mais utilizando técnicas de defesa simples, apesar de valerem apenas um ponto (Kazemi, et al, 2010), o que parece persistir em estudos mais atuais (Tornello, et al, 2014;Falcó, et al, 2014;Kruszewski, et al, 2014;López-López, et al, 2015). Essa diferença, observada na Tabela 3, pode ser parcialmente explicada pelas mudanças das regras da modalidade durante o período entre as competições mencionadas, fato que modifica a estratégia utilizada na luta.…”
Section: Caracterização Do Combate De Tkdunclassified
See 1 more Smart Citation
“…Few studies have been done for match analysis in martial art. The studies found that tactics were used by non-winners during the match was an attacking movements, hence it allowed winners to anticipate and prepare with defence strategies (Asia et al, 2013;Tornello et al, 2014;Kazemi et al, 2006). In taekwondo, attacking and defending tactics are two important strategies that need to be decided by taekwondo players during the match.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of match analysis in aiding the tactical, technical and training plan in sports [1][2][3][4]. Match analysis in sports will help to give information on the playing pattern, physiological and psychological stress of the performers.…”
Section: Introductionmentioning
confidence: 99%